TELEHEALTH AND TELEMEDICINE APPLICATIONS IN THE MANAGEMENT OF DIABETES MELLITUS DURING PANDEMIC COVID 19 : BIBLIOMETRIC ANALYSIS - Nian Afrian Nuari (Lembaga Pengembangan Kinerja Dosen, 2022)
The Covid 19 pandemic of the past three years has necessitated certain modifications to the management strategy, as health care professionals and diabetic patients cannot communicate directly. Technology is used to ensure that the management of Diabetes Mellitus remains intact. Using a bibliometric methodology, this study intends to examine the breadth of research on the application of telehealth to the management of Diabetes Mellitus during the Covid 19 Pandemic. Google scholar, Pubmed, and Science Direct are used to search for research databases, and VOS-viewer is used to retrieve the search results. The analysis of 902 articles from 2020 to 2022 reveals the existence of three clusters (red, green, and blue) that illustrate the relationship between topics. Bibliometric mapping using three distinct visualization techniques, including network visualization, overlay visualization, and density visualization. The most frequent keywords are Covid, Diabetes Mellitus, and Telemedicine. Telemedicine plays an essential role in the care of Diabetes Mellitus during a pandemic since it is simpler to communicate with patients due to limited interaction during lockdown, as seen by the analysis of the visualization above. Telehealth visits could be the subject of research that could be utilized to future studies.